Activation of Molecular Hydrogen by Arylcarbenes. Issue 70 (19th November 2018) - Mendez‐Vega, Enrique; Maehara, Mika; Raut, Akshay Hemant; Mieres‐Perez, Joel; Tsuge, Masashi; Lee, Yuan‐Pern; Sander, Wolfram
Abstract: The hydrogenation reactions of diphenylcarbene1, fluorenylidene2, and dibenzocycloheptadienylidene3 were investigated in solid H2 and D2 matrices and in H2 ‐ and D2 ‐doped argon matrices at cryogenic temperatures. The reactivity of the carbenes towards H2 increases in the order1 <3 <2 . Whereas1 is stable in solid H2, 2 and3 react fast under the same conditions via quantum chemical tunneling. In D2 both1 and3 are stable, whereas2 slowly reacts. The different reactivity of the three carbenes is rationalized in terms of differing carbene stabilization energies. Abstract : How to split a hydrogen molecule? The hydrogenation reactions of three arylcarbenes were studied in low‐temperature matrices. Despite having similar scaffolds, their reactivity toward H2 and D2 is very contrasting.